(untitled) (Global Journal of Science Frontier Research, 2021)
Crisis management, or, in other words, management in the "strong" maneuver mode, refers to the most complex types of organizational management. The large dimensionality of decision-making tasks coupled with a shortage of time put forward an urgent need to automate crisis management procedures. However, such features of crisis management as: weak structuring of the tasks to be solved due to their uniqueness, uncertainty of conditions, volatility of goals (aspects) of management -serve as an obstacle to automation. The ontological approach offers a number of advantages with solutions and problems of crisis management automation. Applying the activity ontology to organizational multi-aspect management, one expands significantly the application field of formalized methods. It makes alternatives more detailed.